Meta-analysis of the influence of I148M variant of patatin-like phospholipase domain containing 3 gene (PNPLA3) on the susceptibility and histological severity of nonalcoholic fatty liver disease - Sookoian, Silvia Cristina (2011)
Our objective was to estimate the strength of the effect of the I148M (rs738409 C/G) patatin-like phospholipase domain containing 3 (PNPLA3) variant on nonalcoholic fatty liver (NAFLD) and disease severity across different populations. We performed a systematic review by a meta-analysis; literature searches identified 16 studies. Our results showed that rs738409 exerted a strong influence not only on liver fat accumulation (GG homozygous showed 73% higher lipid fat content when compared with CC ones, data from 2,937 subjects; P < 1 × 10−9), but also on the susceptibility of a more aggressive disease (GG homozygous had 3.24-fold greater risk of higher necroinflammatory scores and 3.2-fold greater risk of developing fibrosis when compared with CC homozygous; P < 1 × 10−9; data from 1,739 and 2,251 individuals, respectively). Nonalcoholic steatohepatitis (NASH) was more frequently observed in GG than CC homozygous (odds ratio [OR] 3.488, 95% confidence interval [CI] 1.859-6.545, random model; P < 2 × 10−4; data from 2,124 patients). Evaluation of the risk associated with heterozygosity for the variant suggests that the additive genetic model best explains the effect of rs738409 on the susceptibility to develop NAFLD. Nevertheless, carrying two G alleles does not seem to increase the risk of severe histological features. Meta-regression showed a negative correlation between male sex and the effect of rs738409 on liver fat content (slope: −2.45 ± 1.04; P < 0.02). The rs738409 GG genotype versus the CC genotype was associated with a 28% increase in serum alanine aminotransferase levels. Conclusion: By summarizing the amount of evidence, this study provided unequivocal evidence of rs738409 as a strong modifier of the natural history of NAFLD in different populations around the world.